Contemporary Research in Foreign Language Teaching and Learning - Léon-Henri, Dana Di Pardo (Cambridge Scholars Publisher, 2020)
This volume is focused on the teaching and acquisition of language for special, professional or general purposes, as well as the needs and challenges associated with foreign language pedagogy in English for Specific Purposes (ESP) or, more generally, Language for Specific Purposes (LSP). It presents innovative methodology and technology-integrated approaches that will serve to benefit teacher development and assist language practitioners in enhancing student investment and motivation. A pragmatic tool for utilization at the local level, this collection provides an international panorama of lan.